Interplay of Notch and FGF signaling restricts cell fate and MAPK activation in the Drosophila trachea. - Ikeya, T.; Hayashi, S. (Development, 1999)
The patterned branching in the Drosophila tracheal system is triggered by the FGF-like ligand Branchless that activates a receptor tyrosine kinase Breathless and the MAP kinase pathway. A single fusion cell at the tip of each fusion branch expresses the zinc-finger gene escargot, leads branch migration in a stereotypical pattern and contacts with another fusion cell to mediate fusion of the branches. A high level of MAP kinase activation is also limited to the tip of the branches. Restriction of such cell specialization events to the tip is essential for tracheal tubulogenesis. Here we show that Notch signaling plays crucial roles in the singling out process of the fusion cell. We found that Notch is activated in tracheal cells by Branchless signaling through stimulation of ? expression at the tip of tracheal branches and that activated Notch represses the fate of the fusion cell. In addition, Notch is required to restrict activation of MAP kinase to the tip of the branches, in part through the negative regulation of Branchless expression. Notch-mediated lateral inhibition in sending and receiving cells is thus essential to restrict the inductive influence of Branchless on the tracheal tubulogenesis.